DEMOCRATISATION MOVEMENT AND OBSTACLES TO DEMOCRATISATION IN SINGAPORE AND MALAYSIA - Aryanta Nugraha (Jurnal Studi Diplomasi dan Keamanan, 2011)
This article analyses and compares the strenghts and the weaknesses of democratic movements in Singapore and Malaysia. It also hihglights the obstacles of democratisation in both countries. The question that put forward is, why the democratic movements in both countries are weak, unenthusiastic, relatively fragmented. Using Eva Bellin's concept -contingent of democrats, this article argues that the weakness of democratic movements in both countries are influenced by the nature of capitalist development that dominated or at least sponsored by the state. The higher degree of the social classes to the state will be followed by the hihger degree of the fearness of these social class towards the state. It eventually resulted in the lower degree of enthusiastic political activisms from the relevant social classes towards democracy. In overall, the democratic opening in Singapore and Malaysia require structural transformation in the pattern of relations between states and the social classes